Question

( x=a l-m quad y=b m-n, quad z=c n-l )
( z|x| ell+m)+y(m+n)+z(n+ell) )
( Rightarrow quad(a l-m)(l+m)^{0}+(b m-n)(m+n)+(c n-l)(n+e) )
( begin{aligned} text { s) }left(a b^{2}-ln +a ln +m^{2}right) & text { ( }left.b m^{2}-m n+b m n-n^{2}right) &+left(c n^{2}-ln +c n l-l^{2}right) end{aligned} )
( 2+operatorname{atg} A )
( frac{2}{2} quad(a-1) &^{2}+(b-1) m^{2}+(c-1) n^{2} )
( +(a-1) & m+(b-1) m n+(c-1) n ell )
( Rightarrow quad(a-1)(l l+m)+(b-1) M(m+n) )
( +(c-1) n(n+e) )

# 5. If x= al-m, y= 6m-n, z= en-l find the simplest value of x(ltm) + y(m+n) + 3(n+O)

Solution